APLIKASI PERSIAPAN UN DAN UAS TEORI KEJURUAN PADA SMKN-1 PURUK CAHU JURUSAN TKJ BERBASIS ANDROID - Sahay, Abertun Sagit; Saragih, Agus Sehatman; Melati, Erma (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2017)
SMKN-1 Puruk Cahu is one form of a formal education unit that provides vocationaleducation in secondary education as a continuation of junior high school or other equivalent form.TKJ Department is a department that aims to produce graduates who have knowledge and skills inthe field of computers. To pass SMK students must pass the UAS and UN exam. There are fivesubjects tested nationally, namely Indonesian, English, Mathematics, Skills Competency Test andVocational Theory Exam. The Vocational Theory Exam is a vocational theoretical subject wherethis lesson supports the practice of vocational skills. Because so many tests that must be taken bystudents to graduate, then the students must study harder in facing the UN and UAS. Androidprovides an open platform for developers to create apps. With this it is very appropriate ifdevelopers develop applications that can be used by students to assist in facing the preparation ofUN and UAS vocational theory at SMKN-1 Puruk Cahu TKJ majors.Therefore, research can be done with the title of Application Preparation UN and UASVocational Theory At SMKN-1 Puruk Cahu Department of TKJ Based Android using luthermethodology consisting of 6 stages, namely concept, design, collecting material, assembly, testingand distribution.This application was tested using BlackBox testing. This application has twelve menusnamely, dictionary acronym menu, summary menu, download menu of books, collection menu, UNdiscussion menu, UAS discussion menu, quiz menu of class increase, UN quiz menu, UI quiz menu,conversion menu, profile menu and menu help. For further development can add features such asMini Games so as not to be boring.